The effect of age on emotion processing in individuals with mood disorders and in healthy individuals - Gray, Vanessa; Moot, William; Frampton, Christopher M. A.; Douglas, Katie M.; Gallagher, Peter; Jordan, Jennifer; Carter, Janet D.; Inder, Maree; Crowe, Marie; McIntosh, Virginia V. W.; Porter, Richard J. (Frontiers in Psychology, 2024)
This is a provisional file, not the final typeset article or bipolar) were compared with 61 healthy control participants, and in the other, 100 people with bipolar disorder (in various mood states) were tested on the same facial expression recognition task. Repeated measures analysis of variance was used to examine the effects of age and mood disorder diagnosis alongside interactions between individual emotion, age, and mood disorder diagnosis. A positivity effect was associated with increasing age which was evident irrespective of the presence of mood disorder or current mood episode.Results suggest a positivity effect occurring at a relatively early age but with no evidence of a bias towards negative emotions in mood disorder or specifically, in depressed episodes. The positivity effect in emotional processing in aging appears to occur even within people with mood disorders. Further research is needed to understand how this fits with negative biases seen in previous studies in mood disorders.